CORRELATION OF THE USE OF CONTRACEPTIVE PILL COMBINATION TO RISK OF LEIOMYOMA EVENTS IN RSPAL SURABAYA - Belienda Gracella; Sianty Dewi; Lukas Slamet Rihadi (JOURNAL OF WIDYA MEDIKA JUNIOR, 2022)
The use of contraception is important to control population growth, regulate the interval between pregnancies, avoid unwanted births, control the time of birth in a husband and wife relationship and determine the number of children in the family. According to the Central Statistics Agency (BPS) of East Java Province in 2018, the number of active Family Planning (KB) participants of married women of childbearing age who use hormonal contraception in the form of pills was 19.26%, injections were 50.44%, and implants is 11. 45%. Uterine fibroids occur in 20%-25% of women of reproductive age. The prevalence of leiomyoma may increase with hormonal contraceptives containing the hormone estrogen, either pure or combined. Uterine fibroids can affect the quality of life of the sufferer.Purpose: To analyze the relationship between the use of combined pill contraceptives and those who do not use the combined pill contraception in women with the incidence of leiomyoma.Method: This research is an observational analytic carried out retrospectively with a case-control approach. The sampling technique in this study was non-probability sampling, namely purposive sampling. This study uses secondary data, namely medical records of gynecological patients at the RSPAL Dr. Ramelan Surabaya by meeting the inclusion criteria and exclusion criteria. The data collected will be analyzed by looking at whether leiomyoma patients use combined pill contraception.Result: Patients diagnosed with leiomyoma who used the combined pill contraceptive were 48 (63%), while those who did not use the combined pill were 28 (37%). This study's results indicate a significant relationship between the use of combined pill contraceptives and the incidence of leiomyoma (p=0.001).Conclusion: There is a relationship between the use of combined pill contraceptives with the incidence of leiomyoma.